PARE0017 Eular Young Pare: The Voice of Young People with Rheumatic Diseases across Europe. (15th July 2016) - Andersen, J.; Stones, S.; Balazova, P.; Van Nieuwkoop, L.; Papastavrou, T.; Caeyers, N.; Klett, F.
Abstract : Background: The group of Young Patients with Arthritis/Rheumatism in Europe (PARE) in EULAR, the European League Against Rheumatism, is a network of young people, from across Europe, living with a rheumatic or musculoskeletal disease (RMD) and working with a patient organisation in their country. They volunteer their time to represent young people with RMDs within EULAR PARE, advocating for better care, communication and quality of life for individuals, under 35, across Europe. Objectives: When the group was established, objectives were designed to: (1) establish and strengthen national RMD youth groups across Europe; (2) create and support the European network of RMD youth groups to exchange best practices; (3) empower youth leaders; and (4) ensure that the voice of young people with RMDs is heard on all levels in society. Methods: EULAR Young PARE are actively involved in local, national and international activities to support young people with RMDs. Members of EULAR Young PARE developed an action plan to communicate and promote their work, embedding the youth perspective into and supporting all EULAR PARE activities. Results: A strong voice of young people, especially at the Annual European Conference of PARE, has been established, with topics delivered and dedicated to the needs of young people. All PARE activities and projects now entail a young person living with an RMD, feeding back into the Young PARE working group. Furthermore, strengthening collaboration with the EMEUNET network is a leading example of how we learn together. Conclusions: Young PARE have moved forward considerably over the last twelve months, gathering and sharing information about the ways that young people with RMDs are supported in European countries. Now, EULAR Young PARE is continuing to unite patient organisations across Europe, helping to raise awareness and make a difference to young people living with RMDs while challenges remain. It is important to keep the network sustainable, and EULAR Young PARE committed to working on this over the coming years. References: EULAR Young PARE. Available from: http://www.youngpare.org [Accessed 13 December 2015]. Acknowledgement: Special thanks to EULAR and EULAR PARE for supporting the vision of EULAR Young PARE. EULAR Young PARE would also like to acknowledge all of the patient organisations that they continue to work with. Disclosure of Interest: None declared